Specks of Dirt and Tons of Pain: Dosage Distinguishes Impurity From Harm. (August 2019) - Rottman, Joshua; Young, Liane
Levels of moral condemnation often vary with outcome severity (e.g., extreme destruction is morally worse than moderate damage), but this is not always true. We investigated whether judgments of purity transgressions are more or less sensitive to variation in dosage than judgments of harm transgressions. In three studies, adults ( N = 426) made moral evaluations of harm and purity transgressions that systematically varied in dosage (frequency or magnitude). Pairs of low-dosage and high-dosage transgressions were presented such that the same sets of modifiers (e.g., "occasionally" vs. "regularly, " "small" vs. "large") or amounts (e.g., "millimeter" vs. "centimeter") were reused across moral domains. Statistical interactions between domain and dosage indicated robust distinctions between the perceived wrongness of high-dosage and low-dosage harms, whereas moral evaluations of impure acts were considerably less influenced by dosage. Our findings support the existence of a cognitive distinction between purity-based and harm-based morals and challenge current wisdom regarding relationships between intentions and outcomes in moral judgment.